Implementasi Manajemen Riayah di Masjid Attaqwa Wates Ngaliyan dalam Meningkatkan Kenyamanan Jamaah dalam Beribadah - Diyah Fajar Astutik; Siti Prihatiningtyas; Dedy susanto; Lukmanul Hakim (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
Riayah management is an important part of mosque management that focuses on the maintenance and upkeep of mosque facilities and buildings. This study aims to analyze the existing riayah management at the Attaqwa Wates Ngaliyan Mosque and analyze the comfort of the congregation during worship at the Attaqwa Wates Ngaliyan Mosque. The research method used in this study is a descriptive qualitative research method, through a case study approach. Data were collected through direct observation methods, interviews with (the Head of the Mosque Takmir, the Head of the riayah field and the mosque caretaker) and also documentation. The results of the study indicate that the procurement of mosque facilities and infrastructure has been carried out optimally and in accordance with the needs of the congregation. So that the existing facilities are able to support the comfort of the congregation in worship. Meanwhile, riayah management based on the functions of planning, organizing, mobilizing and monitoring has been implemented, but not optimally. Maintenance activities have been carried out but are not supported by written SOPs. Supervision is still reactive and audio comfort is still uneven, which affects the comfort of the congregation.